Studi Empiris Pengaruh Profitabilitas Dan Likuiditas Terhadap Kebijakan Dividen - Adanan Silaban; Niska Trita Olivia Zalukhu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the effect of profitability and liquidity on dividend policy in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Profitability is proxied by using Return On Assets (ROA), liquidity is proxied by using the Current Ratio (CR), and dividend policy is measured by using the Dividend Payout Ratio. Sampling using purposive sampling method, obtained a sample of 90 observations. Data analysis in this study used the SPSS 25 computer program. The results of this study indicate that profitability and liquidity have a positive and significant effect on dividend policy. The results of this study strengthen the results of previous studies. Keywords: Profitability, Liquidity, Dividend Policy.